Notice of Retraction Solar DC Microgrid for Rural Electrification-A Case Study - Debojyoti Sen (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2016)
Notice of Retraction-----------------------------------------------------------------------After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting ijeei.iaes@gmail.com.-----------------------------------------------------------------------Currently around 1.5 billion people worldwide live without access to electricity, and without a concerted effort, this number is not likely to drop. Grid extension is often very costly and not feasible in isolated areas. In such situations, electricity mini-grids can power household use and local businesses. The expansion of rural electrification is occurring mainly under the RGGVY (Rajiv Gandhi Grameen Vidhyutikaran Yojona ) scheme in India. As among all the renewable sources solar is the most explored one, DC micro grid has become one of the most popular and proposed option for rural electrification. Various policies and delivery models are being implemented on DC micro grid. But Is Dc Micro grid really a viable option for rural electrification? This paper focuses on the various socio-economic and even the technical aspect of DC micro Grid to check its viability and the study is aided by survey reports on the same on various rural villages of India. The paper also tried to integrate the schemes that is introduced for rural electrification with DC micro grid and try to analyze whether DC micro Grid is a sustainable option of rural electrification.